Survei Motivasi Peserta Didik dalam Mengikuti Kegiatan Ekstrakurikuler Futsal - Aswanto, Rizal Dwi (Sport Science and Health, 2021)
Abstract: The research design used was survey research with quantitative descriptive research. The research subjects were 100 futsal extracurricular participants in public high schools in Kediri City District. The instrument used was a Likert scale questionnaire. The data analysis used was the percentage technique. From the results of the data analysis, 3 conclusions were obtained, namely: (1) Intrinsic motivation, namely 66 students, 66% were in good category (2) 50% extrinsic motivation of students is in the sufficient category. (3) The overall motivation, namely 70 students, was in the good category.Â Abstrak: Rancangan penelitian ini yang digunakan adalah penelitian survei dengan jenis penelitian disktriptif kuantitatif. Subjek pelitian ini sebanyak 100 orang peserta ekstrakurikuler futsal di SMA Negeri se-Kecamatan Kota kediri. Instrumen yang digunakan yaitu angket skala likert. Analisis data yang digunakan adalah teknik persentase, dari hasil analisis data diperoleh 3 kesimpulan yaitu: (1) Motivasi intrinsik yaitu 66 peserta didik 66% masuk kategori baik. (2) Motivasi ekstrinsik 50 peserta didik 50% masuk kategori cukup. (3) Motivasi keseluruhan yaitu 70 peserta didik 70% masuk kategori baik.